Relationship of Nottingham Prognostic Index with prognostic parameters of breast carcinoma - Zahid Mahmood Akhtar, Rabia Altaf, Muhammad Shahbaz Amin, Seema Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer (BC) is the commonest malignancy in the female and it is gaining its significance due to worldwide rising incidence. It is also important due to 2.5% higher incidence in Pakistan as compared to neighbouring countries. Nottingham prognostic index (NPI) is an important prognostic factor of BC. It provides information about survival and morbidity. There are significant variations in different studies. Aim: To carry out current study relating NPI with various histopathological parameters of BC. Methods: This was a descriptive cross-sectional study. The study was done at the Department of Pathology, King Edward Medical University Lahore with the collaboration of four surgical units of Mayo Hospital Lahore from 2010 to 2019. Total 137 cases of breast carcinoma were included. Information about age, grade, primary tumor size, axillary lymph node status and stage was entered in the pre designed proforma. NPI was calculated as 0.2xtumor size(cm)+lymph node grade. NPI was scored as excellent, good, moderate and poor and its correlation was calculated against primary tumor size, lymph node grade, tumor grade and stage. Results: We studied 137 cases of breast carcinoma with mean age 49.32±11.64 years. Mean NPI was 5.4±1.4 with range of 2.4 to 9.4. NPI scores in poor 65(47.4%) and moderate 61(44.5%) groups were significantly high as compared to good 10(7.3%) and excellent scores 1(0.7%). Most of the cases of poor NPI were in p T3 and p T4 whereas this was p T2 with moderate score. Poor score of NPI was significant in grade 3 which is in contrast to moderate score where grade 2 dominated the picture. Correlation of NPI with LNG was in favor of LNG 1 with good and moderate scores while LNG3 dominated in the poor group. In stage III, 49 cases (35.8%) were seen with poor score of NPI. Conclusion: NPI is an important prognostic parameter and it can be studied with different histopathological parameters to see correlation between them. In the current study majority of the cases of NPI scored at poor and moderate levels. Correlation coefficient was linear, strong and positive especially with LNG. Mean NPI has ascending correlation with these parameters. Thus NPI can be used as a prognostic indicator when comparing with histopathological parameters of BC.